Normative fitness values: Among teenage male competitive hockey players - Bent, J.; DeBeliso, M. (The Sport Journal, 2020)
Muscular strength, endurance and power are important attributes in many sports. Fitness testing norms are published for a variety of sports across a range of age groups and playing levels, however they do not currently exist for competitive high school aged hockey players. Purpose: This study reported lower body power (standing long jump-SLJ), upper body muscular endurance (bench press-BP and pull ups-PU), and lower body strength (3RM back squat-3RM-BSQ) data collected over three years at the beginning of each hockey season for the purpose establishing an initial set of fitness norms for competitive high school aged hockey players. Methods: Ninety-eight Canadian (U17AAA = 55; U18AAA = 43) high school male participants competing in midget AAA hockey were tested prior to the beginning of each season in September during the 2015-2017 hockey seasons with a host of fitness tests. Means, standard deviations and percentile ranks were calculated for the SLJ, maximum BP repetitions at 75% of body weight (BP-75%), PU, and 3-RM BSQ for both U17AAA and U18AAA hockey players. Results: Means, standard deviations for each player grouping were as follows. U17AAA (SLJ=234.7±15.7, BP-75%= 9.2±5.4, PU= 9.5±4.5, 3-RM-BSQ=108.0±15.4) and U18AAA (SLJ=235.7±16.6, BP-75%=13.0±6.7, PU=10.0±5.2, 3-RM-BSQ=120.4±21.0). Conclusion: The data presented provides a preliminary set of physical performance benchmarks for coaches and players to utilize in order to develop an athletic profile for athletes aspiring to compete in hockey at the AAA level and beyond.